Arbitration Award of ICSID on the Investment Disputes of Churchill Mining PLC v. Republic of Indonesia - Gunawan, Yordan (Hasanuddin Law Review, 2017)
The research is aimed at analyzing the ICSID (International Centre Settlement Investment Dispute) decision in solving a dispute between Churchill Mining PLC and the Government of the Republic of Indonesia. The case brought to the public attention, because mining license owned by PT. Ridlatama which acquired from Churchill Mining PLC had been revocated. Churchill Mining PLC holds 75% share of PT. Ridlatama and it suffered losses caused by the revocation of its mining license. Churchill Mining PLC filed the case to the local court but it failed. Churchill Mining PLC then sought ruling from International arbitration or ICSID. On December 6, 2016, ICSID issued a decision that clearly threw out Churchill Mining PLC claim. ICSID, the World Bank court, ordered the firm to pay a total of US$.9.446.528 in cost to the Government of the Republic of Indonesia. It is based on the evidences that the UK-Australia company did the fraud and had document forgery of coal mining permit in East Kutai, Indonesia. So the firm has violated the Bilateral Investment Treaties between Indonesia-UK and Indonesia-Australia.